Radio-quiet quasars in the VIDEO survey: evidence for AGN-powered radio emission at S1.4 GHz < 1 mJy - White, Sarah; Jarvis, M.; Häußler, B.; Maddox, N. (Oxford University Press, 2015)
Understanding the interplay between black-hole accretion and star formation, and how to disentangle the two, is crucial to our understanding of galaxy formation and evolution. To investigate, we use a combination of optical and near-infrared photometry to select a sample of 74 quasars from the VISTA Deep Extragalactic Observations (VIDEO) survey, over 1 deg2. The depth of VIDEO allows us to study very low accretion rates and/or lower-mass black holes, and 26 per cent of the candidate quasar sample has been spectroscopically confirmed. We use a radio-stacking technique to sample below the nominal flux-density threshold using data from the Very Large Array at 1.4 GHz and find, in agreement with other work, that a power-law fit to the quasar-related radio source counts is inadequate at low flux density. By comparing with a control sample of galaxies (where we match in terms of stellar mass), and by estimating the star formation rate, we suggest that this radio emission is predominantly caused by accretion activity rather than star-formation activity.